Agrobacterium Mediated Transformation of Maize (Zea mays L.) - H. Rahnama (Journal of Sciences, Islamic Republic of Iran)
Agrobacterium tumefaciens mediated transformation may offer a better alternative than the biolistic gun for genetic transformation of maize plants. This gene delivery system results in a greater proportion of stable, low-copy number transgenic events than does the biolistic gun, and is highly efficient. In the present work, we studied maize transformation using A. tumefaciens by identifying some important factors that affect transformation efficiency subsequent tissue culture and regeneration of transgenic plants. Although, all genotypes produced embryogenic calli, S61 and A188 lines had higher percent (75% and 71% respectively) of regeneration than the other ones. Transformant events obtained when immature embryos (1.5-2 mm) were inoculated with A. tumefaciens LBA4404 harboring a standard binary vector pCAMBIA3301 after 72 h pretreatment culture of the embryos. Polymerase chain reaction (PCR) confirmed the presence of the gus and bar genes in the genome of regenerated plants. The transformation frequency (the number of independent, PCR-positive transgenic plants per 100 embryos infected) was 6.45% for S61 genotype. Therefore, our results identified suitable genotype (S61), embryo size (1.5-2 mm), A. tumefaciens strain (LBA4404), pretreatment culture, and appropriate antibiotic (Timentin) for Agrobacterium mediated transformation of Z. mays.